2014
DOI: 10.4236/jwarp.2014.612106
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Temperature, Nitrogen, and Zooplankton on Growth and Protein and Carbohydrate Content of Cyanobacteria from Western Lake Erie

Abstract: Harmful algal blooms (HABs) in freshwater ecosystems, especially of cyanobacterial species, are becoming more frequent and expanding geographically, including in Lake Erie in North America. HABs are the result of complex and synergistic environmental factors, though N or P eutrophication is a leading cause. With global mean temperatures expected to increase an additional 2˚C -5˚C by 2100, cyanobacterial blooms are predicted to increase even more, given their typically-high temperature optimum for growth. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…According to our investigation of the pond water plankton community structure, we found the Cyanophyta and Chlorophyta phylas dominated the phytoplankton, while Rotifers and Protozoa were abundant in the zooplankton, and shows a clear seasonal change. Enhanced sunshine, higher nutritional salts and fish excretion all contributed to increasing phytoplankton density in the early stages of culture (Bista et al, 2014). As fish grow, the amount of bait increases, residual bait and extra excretion continue to breakdown, resulting in eutrophication, which is exacerbated by rising temperatures and other factors (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to our investigation of the pond water plankton community structure, we found the Cyanophyta and Chlorophyta phylas dominated the phytoplankton, while Rotifers and Protozoa were abundant in the zooplankton, and shows a clear seasonal change. Enhanced sunshine, higher nutritional salts and fish excretion all contributed to increasing phytoplankton density in the early stages of culture (Bista et al, 2014). As fish grow, the amount of bait increases, residual bait and extra excretion continue to breakdown, resulting in eutrophication, which is exacerbated by rising temperatures and other factors (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While algae proliferate and blooms form as a result of various environmental factors [15][16][17][18], accumulating evidence has indicated that climate conditions may be the main limiting factor of algal bloom formation when a lake maintains a high level of eutrophication [5,19,20]. Under favorable climate conditions, algal cells can proliferate rapidly and form algal blooms in eutrophic lakes [2].…”
Section: Introductionmentioning
confidence: 99%